(3GKQ JOQjHGJ GdJhGRf h GdJhGab GdMQcj Ydi GdGOGA GdegGQj HGdbOe GdVYjaI dOi HQGYe cQI GdbOe (B( (3aFI (B13 (3SfI (B) : (3OQGSI ejOGfjI Ydi aQjb GJMGO GdTGhjI ddaFI Gbd ef (B13 (3SfI s - (3eLQGdj, GMeO s; (3TfGJj, GMeOs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2021)
(3MGhdfG ef NdGd gPg GdOQGSI GdcTa Yf (B"(3CKQ JOQjHGJ GdJhGRf hGdJhGab GdMQcj Ydi GdCOGA GdegGQj HGdbOe GdVYjaI dOi HQGYe cQI GdbOe (Bu13 "(3, ef NdGd JbOje JOQjHGJ GdJhGRf hGdJhGab GdMQcj HGdWQa GdYcSj dCaQGO GdeLehYI GdJLQjHjI eOeLI HGdcQI hOhf cQI, YcS CaQGO GdeLehYI GdVGHWI Cjf Je JbOje GdJOQjHGJ MSH GdeYJGO Cj HGdbOe GdeaVdI dOjge, hPdc HYO GdGWdGY Ydi GdNdajI GdfXQjI heSM ddOQGSGJ GdSGHbI hGdeTGHgI, heSJOdjf Ydi HYV GdCacGQ hGdJhUjGJ hGdGbJQGMGJ GdSGHbI GdJj JfGhdJ RGhjI GdHMK aj GdbOQGJ GdMQcjI hGdCOGA GdegGQj, hGSJNOe GdHGMK GdefgL GdJLQjHj Ph JUeje GdeLehYGJ GdeJcGaFI, hYdi YjfI HMK Je GNJjGQgG HGdWQjbI GdbUOjI echfI ef (B(30) (3dGYHG, Je JbSjege Edi eLehYJjf, (B(15) (3dGYH eLehYI JLQjHjI h(B(15) (3dGYH eLehYI VGHWI, hJhUdJ GdOQGSI Edi GdfJGFL GdJGdjI(B: " (3JhLO aQhb PGJ OdGdI EMUGFjI Hjf GdbjGSGJ GdbHdjI hGdHYOjI aj UaJj GdJhGRf hGdJhGab GdMQcj dcdG GdeLehYJjf GdJLQjHjI hGdVGHWI, dcf HfSH JWhQ eJaGhJI dUGdM GdeLehYI GdJLQjHjI(B. " (3dG JhLO aQhb PGJ OdGdI EMUGFjI Hjf GdbjGSGJ GdbHdjI hGdHYOjI ddegGQGJ bjO GdOQGSI JeQjQ GdcQI, JfWjW GdcQI HGdeQI, OMQLI GdcQI Hjf GdThGNU, JUhjH GdcQI ef GdKHGJ HGdbOe GdVYjaI dOi CaQGO GdeLehYI GdVGHWI(B. " (3hLhO aQhb PGJ OdGdI EMUGFjI Hjf GdbjGSGJ GdbHdjI hGdHYOjI aj egGQI Qcd GdcQI dCHYO eSGaI HGdbOe GdVYjaI dOi CaQGO GdYjfI GdVGHWI(B. " (3hLhO aQhb PGJ OdGdI EMUGFjI Hjf GdbjGSGJ GdbHdjI hGdHYOjI ddegGQGJ GdCSGSjI bjO GdOQGSI JeQjQ GdcQI, JfWjW GdcQI HGdeQI, Qcd GdcQI dCHYO eSGaI, OMQLI GdcQI Hjf GdThGNU, JUhjH GdcQI ef GdKHGJ HGdbOe GdVYjaI dOi CaQGO GdYjfI GdJLQjHjI(B. " (3hLhO aQhb PGJ OdGdI EMUGFjI Hjf GdbjGSGJ GdbHdjI hGdHYOjI ddegGQGJ GdCSGSjI bjO GdOQGSI JeQjQ GdcQI, JfWjW GdcQI HGdeQI, Qcd GdcQI dCHYO eSGaI, OMQLI GdcQI Hjf GdThGNU, JUhjH GdcQI ef GdKHGJ HGdbOe GdeaVdI dOi CaQGO GdYjfI GdJLQjHjI, eG jDcO Cf COGA GdhGLHGJ GdegGQjI HGdbOe GdZjQ eaVdI eOeLI eY GdYfGUQ GdMQcjI GdeJONdI aj GdCOGA ef JhGRf MQcj, hJhGab MQcj jDKQ EjLGHG Ydi aYGdjI GdCOGA HGdbOejf, cfJjLI dGfJbGd CKQ GdJYdje hGdJOQjH ef GdbOe GdZjQ eejRI ddbOe GdeejRI(B. (3GdcdeGJ GdOGdI(B: (3GdJhGRf GdMQcj(B/ (3GdJhGab GdMQcj(B/ (3GdCOGA GdegGQj(B/ (3GdegGQGJ GdCSGSjI aj cQI GdbOe(B/ (3GdbOe GdVYjaI(B/ (3GdbOe GdeejRI(B/ (3HQGYe cQI GdbOe(B. s
(3OcJhQGIs
Keywords: (3GdJMVjQ GdHOfj ddehGgH GdTGHIs